Use of Botanical Pesticides in Agriculture as an Alternative to Synthetic Pesticides - Ngegba, Patrick Maada; Cui, Gaofeng; Khalid, Muhammad Zaryab; Zhong, Guohua (Agriculture (Basel), 2022)
Pest management is being confronted with immense economic and environmental issues worldwide because of massive utilization and over-reliance on pesticides. The non-target toxicity, residual consequence, and challenging biodegradability of these synthetic pesticides have become a serious concern, which urgently requires the alternative and prompt adoption of sustainable and cost-effective pest control measures. Increasing attention in environmental safety has triggered interest in pest control approaches through eco-friendly plant-based pesticides. Botanical pesticidal constituents are effective against myriads of destructive pests and diseases. More importantly, they are widely available, inexpensive, accessible, rapidly biodegradable, and have little toxicity to beneficiary agents. The phytochemical compositions in diverse plant species are responsible for their varying mechanisms of action against pests and diseases. However, difficulties in their formulation and insufficient appropriate chemical data have led to a low level of acceptance and adoption globally. Therefore, the review seeks to highlight the status, phytochemical compositions, insecticidal mechanisms, and challenges of plant-based pesticide usage in sustainable agricultural production.